Facet for Anomalous Accessory Articulation of the Coracoid Process of Scapula in the North Indian Region: Prevalence and Clinical Significance - Sehgal Garima; Rani Anita; Chopra Jyoti; Kumar Navneet (Advancement and New Understanding in Medical Science Vol. 9, 2024)
Coracoclavicular (CCJ) joint a diarthrodial synovial articulation sometimes exists between the conoid tubercle of the clavicle & superior surface of the coracoid process. It presents with a variable frequency ranging between 0.55% and 30%. This unique entity is usually asymptomatic but may sometimes present with pain or predispose to arthritic changes in neighbouring joints of the shoulder region. The study was undertaken to find out the prevalence of this joint in the Indian population from osteological samples and included 500 scapulae; 250 right and 250 on the left side. The observations and analysis were done during a 6 month period from June 2017- November 2017. Evidence of CCJ was obtained in the form of definitive facets on the superior surface of the coracoid process. The presence of facets for the joint was observed in 21.8% with a higher proportion on the left side (26%) as compared to the right (17.6%). Facets are presented with a spectrum of shapes and surface features. CCJ is not rare and likely to have an acquired etiology favoured by genetic and environmental factors. We would like to propose that the coracoclavicular joint is not rare, but rather, a common variant of the pectoral girdle. The facets displayed distinctive shapes with unique surface features and surface projection. On the basis of these variations in the morphology of the articular surfaces, we would like to suggest an acquired etiology in the formation of these joints.